PSYCHOLOGICAL METHODS OF PSYCHOLOGICAL PREPARATION OF MILITARY PERSONNEL FOR MILITARY DISCIPLINE IN COMBAT SITUATIONS (American Journal of Pedagogical and Educational Research, 2022)
In this article, psychological methods of psychological preparation of military personnel for military discipline in combat situations were discussed.